The Correlation Between Quality of Life and Positive Psychological Resources in Cancer Patients: A Meta-Analysis - Zhao, Xinxin; Tong, Siqi; Yang, Ye (Frontiers in Psychology, 2022)
Purpose: The purpose of this study was to assess the evidence of the association between positive psychological resources and quality of life in cancer patients. Methods: Electronic search was performed to retrieve articles from PubMed, Web of Science, Embase, CNKI, and CBM (from inception to April 7, 2022). Summary correlation coefficient (r) values were extracted from each study, and 95% confidence intervals (95%CIs) were calculated by the random-effect model. Subgroup and sensitivity analyses were performed to investigate potential heterogeneity. Results: Sixty-six articles were included in the present study. The pooled r for resilience was 0.71 (95%CI: 0.55, 0.87), hope 0.50 (95%CI: 0.43, 0.56), self-efficacy 0.53 (95%CI: 0.46, 0.61), self-esteem 0.46 (95%CI: 0.28, 0.63) and optimism 0.30 (95%CI: 0.19, 0.40). For subgroup analysis, no significant differences were found between minors and adults. Conclusion: Our study indicated that resilience, hope, optimism, self-esteem, and self-efficacy were positively correlated with quality of life in cancer patients. Therefore, interventions programs should be focused on increasing state-like positive psychological resources to improve the quality of life in cancer patients.